Bird clinic - Abu, Jalila; Ismail, Siti Sarismahanim; Abdullah, Aishah; Abdullah, Abraham Gabriel (Universiti Putra Malaysia Press, 2015)
The University Veterinary Teaching Hospital (UVH) located in Universiti Putra Malaysia Serdang has a bird clinic. This is the clinic of choice for the public, pet owners and veterinarians for sick birds and injured wild birds. A bird’s anatomy is quite different from a cat or dog, so it requires specialized care administered by a qualified bird doctor (avian veterinarian). The care provided by the team include something as simple as grooming (wing clipping, toe nail trimming, beak trimming) and further treatment for simple cases to complicated orthopedic or soft tissue surgeries. Fracture cases are commonly seen.